María José ÁLVAREZ FAEDO, «A Bio-Bibliography of Eighteenth-Century Religious Women in England and Spain». Lewiston, Queenston y Lampeter, The Edwen Mellen Press, 2005. 131 págs. (Colección Studies in Women and Religion, vol. 44). - Bastida Rodríguez, Patricia (Cuadernos de Estudios del Siglo XVIII, 2005)
SIN RESUMEN